Portrayal of women’s images in television dramas: a Malaysian case - Ibrahim, Faridah; Yunus, Norzita; Halem Shah, Dil Froz Jan Sayed; Ilias, Munirah; Ahmad Mokhtar, Amli Hazlin (2017)
Current situations brought about by globalisation and sophisticated innovations in new technology not only have created a new understanding of the world around us but also conscientiously sensitised society, particularly the women towards a more active role in shaping their world.An important contributory factor that can determine the success of women is their centrality in the media, through media positions held or through media images portrayed.What this paper has endeavoured to show is the portrayal of women in the media particularly, television dramas.In today’s scenario, the role of women keeps changing, so does the portrayal of women’s images in television dramas.This paper, based on a qualitative content analysis study of five popular Malaysian television dramas, found that the stereotypical generalizations of women’s images are still existing but to a lesser degree.